Comparison Between Mini Plate Versus Trapezoidal Plate in Management of Condylar Fracture - Lajpat, Ziaur Rahman Khan, Fida Hussain, Suneel Kumar Punjabi, Arsala Urooj, Talib Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the clinical outcomes between the Miniplates versus Trapezoidal plates in terms of pain, mouth opening and malocclusion. Methodology: A total of 34 patients were categorized into two Groups according to convenient Sampling Methods. Group A was treated with Miniplates and Group B was treated with Trapezoidal Plates. Diagnosis of condylar fracture was made through clinical examination, Orthopantomogram (OPG), P.A view of face and 3D CT scans where indicated. After surgery postoperative pain, mouth opening and malocclusion were recorded at interval of 3, 7, 14 and 21 days. Results: Mean age of the patients of group A was 30.39+10.91 years and mean age of patients of group B was 29.05+7.25 years. Males were in majority in both groups as 70.6% were in group A and 88.2% were in group B. Preoperatively most of the patients were presented with severe pain in both groups as 47.1% in group A and 52.9% in group B. Post-operative pain on day 3 was in moderate presentation in both groups, on day 7 and day 14 pain was mild in both groups and on day 21 there was no pain in either groups. Malocclusion in Group A on day 3 was in 29.4% and 11.85% in group B. At Day 21 both groups were recorded with no malocclusion. But patients treated with trapezoidal plate achieved stability earlier than those treated with miniplates. Conclusion: Trapezoidal plate has been found to be more effective. There was an improvement in mouth opening and occlusion in the immediate postoperative period. However findings were statistically insignificant.